Groundwater response to tidal fluctuations in wedge-shaped confined aquifers - Cuello, Julián Eduardo (2017)
Most of the analytical solutions to describe tideinduced head fluctuations assume that the coastal aquifer has a constant thickness. These solutions have been applied in many practical problems ignoring possible changes in aquifer thickness, which may lead to wrong estimates of the hydraulic parameters. In this study, a new analytical solution to describe tide-induced head fluctuations in a wedge-shaped coastal aquifer is presented. The proposed model assumes that the aquifer thickness decreases with the distance from the coastline. A closed-form analytical solution is obtained by solving a boundary-value problem with both a separation of variables method and a change of variables method. The analytical solution indicates that wedging significantly enhances the amplitude of the induced heads in the aquifer. However, the effect on time lag is almost negligible, particularly near the coast. The slope factor, which quantifies the degree of heterogeneity of the aquifer, is obtained and analyzed for a number of hypothetical scenarios. The slope factor provides a simple criterion to detect a possible wedging of the coastal aquifer.